Th1/Th2 profile in patients suffering with osteoarthritis and rheumatoid arthritis: An analytical observational study - Yatendra Singh; Shadab Ahmad Khan; Mohammad Owais; Mazhar Abbas; Anjum Parvez; Athar Kamal (Wolters Kluwer Medknow Publications, 2014)
Aims: To compare the cytokine (Th1/Th2) profile in serum as well as in synovial fluid of patients suffering with osteoarthritis (OA) and rheumatoid arthritis (RA). Settings and Design: Hospital-based analytical observational study. Materials and Methods: The present study comprised of 70 patients of arthritis, out of which, 40 patients were patients suffering from RA and 30 patients suffering from OA. Patients fulfilling the revised ARA Criteria for the Classification of Rheumatoid Arthritis are diagnosed as a case of RA and recruited for this study. Patients fulfilling the clinical and radiological features of osteoarthritis included in the study. Cytokine assay estimated using Western Blot (Immuno-blot transfer). Statistical Analysis Used: Analysis was performed using SPSS version 16.0 Statistical package for windows (SPSS, Chicago, IL). Results: Arthritis is commonly seen in females than males. Proinflammatory cytokines (IL-1, IL-2 and IFN-γ), anti-inflammatory cytokines (IL-4 and IL-10), regulatory cytokine (TGF-β) of blood as well as serum levels were raised in RA patients as compared with OA patients (P < 0.01). Tumor necrosis factor (TNF-α), an proinflammatory cytokine, levels were also raised significantly in OA. Conclusions: Our study shows that both Th1 and Th2 cells derived inflammatory markers as well as levels of IL-1 and TNF-α (both blood as well as synovial fluid) were significantly raised in RA as compared with OA patients. Thus, high levels of these substances have been found in inflammatory arthropathies, in particular in those characterized by a more aggressive and destructive outcome, such as RA.